Diagnosis and Treatment of Adolescent Polycystic Ovary syndrome:A Review - Zhang Y; Yang K; Fan T; Zheng D; Liu H (International Journal of Women's Health)
Yaoyang Zhang,1,* Kaiyu Yang,1,2,* Ting Fan,1,* Dongying Zheng,1 Hongxiu Liu1 1Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, 116000, People’s Republic of China; 2Department of Obstetrics and Gynecology, Changchun Obstetrics and Gynecology Hospital, Changchun, Jilin, 130000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dongying Zheng; Hongxiu Liu, Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Dalian Medical University, 467 Zhongshan Road, Shahekou District, Dalian, Liaoning, 116023, People’s Republic of China, Email dongyingzheng@dmu.edu.cn; huakaifang2006@126.comAbstract: Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder among women of reproductive age. Diagnosing adolescent PCOS is challenging due to the overlap between adult PCOS diagnostic criteria and normal physiological changes in adolescence. This review examines the diagnosis and treatment strategies for adolescent PCOS. The diagnosis of adolescent PCOS should meet two primary criteria—ovulatory dysfunction and biochemical or clinical hyperandrogenism—after excluding other causes. Defining these criteria accurately aids in early diagnosis and management of adolescent PCOS. However, due to limited research, age-specific diagnostic standards remain lacking. Once diagnosed, timely interventions—such as lifestyle, exercise, and dietary changes, along with targeted treatments like metformin and antiandrogens—should be initiated. In addition, the management of adolescent PCOS presents several challenges, including the absence of standardized medication guidelines, adolescent psychological factors that may impede adherence to dietary and exercise recommendations, and parental concerns about the long-term effects of medication on bone health and metabolism. Therefore, additional research is required to establish optimal management protocols to enhance patients’ quality of life and prevent complications.Keywords: PCOS, teenagers, diagnosis, treatment, adolescent PCOS